EVALUASI PACKABILITY RANCANGAN PROTOTIPE SHELTER EVAKUASI BENCANA CAREDs - Yulius, Reynard; Gunawan, Yenny (Jurnal Riset Arsitektur, 2023)
Abstract - The follow-up study “Evaluation of CAREDs SEB18,017 Disaster Evacuation Shelter PrototypeDesign Based on Constructability Trials” is a SEB18,017 design development research that uses a pop-upconcept to the construction feasibility stage. The development that has been carried out uses a 1:2 scalemockup so that there are still details that need to be developed to a 1:1 scale. The problems that arise arerelated to the structural connection system and material selection. In addition, the design development has notbeen tested in terms of adaptability regarding packability and fabricated material systems.Emergency shelter is a temporary shelter for handling post-natural disasters. Emergency shelter is important tobe prepared and provided for victims who need a place to stay after their homes are damaged due to naturaldisasters that occured. Emergency shelter design must be able to provide a safe, healthy and privateenvironment for disaster victims. In addition, the design of emergency shelters must also be able to be easilyprepared by users in a fairly short amount of time, have an easy yet ef ective packaging, and ef icient mobilityto places where disasters occur.Keywords: emergency shelter, pop-up, CAREDs, adaptability, ef iciency, packability